59 I am a patient, let me out of here. a leadership initiative to improve patient flow at weekends. (3rd November 2019) - Almond, K; Sheriff, Najade; Chan, Weng; Osanlou, Orod
Abstract : Background: Following the initial successful implementation of weekend discharge ward rounds by a former chief registrar, we reviewed a 2 year period of whether implementing discharge ward rounds is effective for improving patient flow, and has it sustained increasing the number of 'well' patients discharged over weekends/bank holidays. Methods: From 1st April 2017- 31st March 2019, we reviewed the number of medical discharges facilitated by the discharge ward round on weekend/bank holidays, and a mean figure of discharges/day produced. Dates where no named discharge registrar/clinician logged on the trust system have been excluded. Results: Over the time period, mean number of discharges/day was 2.94. Over the winter months November to February, this figure increased to 3.06 discharges/day. Data collected prior to the implementation of the ward round (May-July 2016) was 1.4 discharges/day. This shows the discharges/day more than doubling since implementation. The original data (6 months post initial implementation) showed a discharges rate of 4.625 discharges/day. Therefore over time the effectiveness of the ward round has decreased, however still shows significant improvement. Conclusions: Weekend discharge ward rounds are effective in increasing the number of 'well' inpatients discharged over weekends. This Results in: patients discharged home/to family members; improves patient flow; provides significant savings for the hospital trust. The number of discharges has decreased since initial implementation, which is a difficulty of sustaining quality improvements over a large time scale. Ways to improve/sustain the improvement need to be explored, with suitable patients identified prior to the weekend effectively. The improvement shown in this study provides evidence for expansion of weekend discharge ward rounds to other trusts, enabling regions and the NHS as a whole to get well patients home, and provide improvements in bed flow and cost savings for the NHS.